Counterfactual thinking about controllable events - BYRNE, RUTH MARY JOSEPHINE (My University, 2000)
When people think about what might have been, they mentally undo controllable rather than uncontrollable events. We report the results of two experiments in which we examined this controllability effect in counterfactual thinking. The experiments show that the mutability of controllable events is influenced by the perceived appropriateness or inappropriateness of the events. The first experiment shows that people change inappropriate controllable actions more than appropriate controllable ones. The second experiment shows that people mutate inappropriate controllable events whether the outcome is exceptional or normal with respect to intrapersonal habitual norms, and whether the outcome is positive or negative. We discuss the implications for alternative theories of counterfactual thinking.
PUBLISHED
Keywords: Psychology